Area-Based Socioeconomic Status Measures and Incidence of Community-Associated ESBL-Producing Enterobacteriaceae, 2017. (October 2020) - Reses, Hannah E.; Brown, Cedric; Dumyati, Ghinwa; Kainer, Marion; Muleta, Daniel; Duffy, Nadezhda; See, Isaac
Abstract : Background: Extended-spectrum β-lactamase–producing Enterobacteriaceae (ESBL-Ent) have emerged as a significant antimicrobial-resistance threat in the community in recent years. To better characterize ESBL-Ent in the community, we examined associations between community-associated ESBL-Ent incidence rates and area-based socioeconomic status (SES) characteristics. Methods: Cases were identified through active, laboratory- and population-based surveillance for ESBL-Ent in 3 Emerging Infections Program (EIP) sites (New Mexico, New York, and Tennessee) from October through December 2017. We defined a case as first isolation of Escherichia coli, Klebsiella pneumoniae, or K. oxytoca from a normally sterile body specimen or urine in a surveillance-site resident, with resistance to ≥1 extended-spectrum cephalosporin and nonresistance to all carbapenems tested. Epidemiologic data were abstracted from medical records. Cases were considered community associated if no significant prior healthcare exposures (ie, inpatient healthcare facility stay, surgery, chronic dialysis, indwelling devices, or external catheters) were documented. Case residential addresses were geocoded and linked to US Census Bureau data to obtain census-tract level SES measures. Census tracts were dichotomized by the percentage living in rural areas (0–49% or ≥50%); census tracts were stratified into quartiles for all other characteristics. Incidence rate ratios (IRR) for each measure, controlling for EIP site, were calculated using Poisson regression. Results: Among 742 ESBL-Ent cases with medical records available, 355 (47.1%) were community associated; of these, 327 case addresses (92.1%) were successfully geocoded. The combined annualized 2017 incidence rate for community-associated ESBL-Ent was 83.2 cases per 100, 000 persons. The highest incidence of community-associated ESBL-Ent was seen in census tracts with the lowest median income (IRR, 1.4; 95% CI, 1.0–2.0) and with the highest percentages of persons without health insurance (IRR, 1.3; 95% CI, 1.0–1.7), with <12th-grade education (IRR, 1.5; 95% CI, 1.1–2.1), living in urban areas (IRR, 1.5; 95% CI, 1.0–2.2), foreign-born (IRR, 1.4; 95% CI, 1.0–2.0), or speaking limited English (IRR, 1.5; 95% CI, 1.1–2.0). There were no significant differences across quartiles for population density, income inequality, the percentage of the population living below poverty, or the percentage of households with crowding (>1 occupant or room). Conclusions: Social determinants of health, such as coverage for healthcare, appear to be important contributors to community-associated ESBL-Ent transmission. Higher rates in areas with more foreign-born persons and persons with limited English proficiency suggest a role for recent travel in importation and spread in specific communities. These findings provide additional information about the epidemiology of ESBL-Ent in the community and have potential implications for control efforts. Funding: None Disclosures: None